2007
DOI: 10.1016/j.midw.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety and feelings of control during labour: A study of Chinese first-time pregnant women

Abstract: midwives should work with women to enhance their personal control during labour and satisfaction with their birth. The insignificant relationship between attendance at antenatal classes and feelings of control suggests the need to evaluate the content of childbirth education in order to empower women's control during labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 46 publications
(69 reference statements)
3
74
0
2
Order By: Relevance
“…Mulder et al (31) showed that high levels of anxiety and stress were accompanied by an increasing probability of preterm labor, delivery of underweight babies, spontaneous abortion, or deformities of the newborn. This correlates with many other studies (16,17,(32)(33)(34). The probable mechanism can be described as follows: anxiety, especially when it persists, affects the autonomous nervous system.…”
Section: Discussionsupporting
confidence: 88%
“…Mulder et al (31) showed that high levels of anxiety and stress were accompanied by an increasing probability of preterm labor, delivery of underweight babies, spontaneous abortion, or deformities of the newborn. This correlates with many other studies (16,17,(32)(33)(34). The probable mechanism can be described as follows: anxiety, especially when it persists, affects the autonomous nervous system.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the result of this study could support the use of soothing music together with other nursing interventions in reducing the pain experienced by women during the latent phase of labor. However, it is essential to note that music intervention was administered only during the latent phase of labor, pain increases as labor progresses [4,5] and the need for pain relief is of its greater importance. With that, further studies ascertaining whether music would still offer pain relief/reduction during the late phases maybe conducted.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In a study by Stark et al, on pregnant women in US, significant relationship has been found between perceived stress and negative spiritual growth, interpersonal relationships, and stress management. 17 However, according to surveys conducted by the researcher, the relationship between health promotion lifestyle and the perceived stress in Iran has not been studied.…”
Section: Introductionmentioning
confidence: 99%